Peer support work : practice, training & implementation - Mahon, Daryl (Emerald Publishing Limited, 2024)
As health and social care policy evolves, peer support is an increasingly recognised method to help improve the outcomes of care by drawing on those with lived experience. However, despite the establishment of a research basis that demonstrates the methods' value in care, implementation of lived experiences of peers in practice contexts faces difficulties. To aid the progress of peer support care, Peer Support Work highlights the experiences of contributors who work or study social care and have lived experience with mental health, substance use, homelessness, criminal justice, and migration. Beginning with the historical context of peer support and moving through the practical implementation of peer support into policy and organizational contexts, this innovative title draws on the contributors' collective experiences, supported by rigorous academic research, to distil the outcomes, benefits, training and implementation challenges within this emerging practice and research context. Researchers interested in moving the field forward will benefit from this comprehensive analysis of the existing research on peer support work. The input from contributors with lived experience makes this unique title an excellent resource for policymakers in addition to academics.
Keywords: Peer counseling.; Psychology, Psychotherapy -- Counseling.; Counselling and care of students.; Psychotherapy: counselling.; elektronické knihy; electronic books